STRUCTURAL FEATURES OF DIPLOMATIC DOCUMENTS - Abdullayeva Diyora (PEDAGOGS, 2024)
Abstract. The article reveals the content of the concept of "diplomatic document", considers the main types and stylistic features diplomatic documents, related, first of all, to their functions and target audience. target audience. The author carries out a quantitative analysis of the lexicon and emphasizes the peculiarities of the use of lexical units, some of which reveal the specifics of the state's foreign policy.